2020
DOI: 10.1167/iovs.61.4.36
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Visual Function Outside the Area of Atrophy Defined by Short-Wavelength Fundus Autofluorescence in Stargardt Disease

Abstract: To examine the extent of visual function abnormality outside the dark lesion on short-wavelength fundus autofluorescence (SW-AF), and its correlation with background SW-AF features and optical coherence tomography (OCT) in recessive Stargardt disease (STGD1) METHODS. Forty-nine eyes of 25 participants in the ProgStar (the Natural History of the Progression of Atrophy Secondary to Stargardt Disease) study at our center were included. Patients underwent microperimetry (both threshold and dense scotoma mapping), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…2018-001496-20]) as outcome measures. While DDAF in STGD1 is well established in terms of reproducibility and progression rates ( 8 , 21 ), the boundaries of absolute scotomata may exceed the boundaries of DDAF in STGD1 (in contrast to age-related macular degeneration) ( 9 , 22 ). Thus, the application of DDAF as a surrogate of disease severity in STGD1 may represent the trailing edge of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2018-001496-20]) as outcome measures. While DDAF in STGD1 is well established in terms of reproducibility and progression rates ( 8 , 21 ), the boundaries of absolute scotomata may exceed the boundaries of DDAF in STGD1 (in contrast to age-related macular degeneration) ( 9 , 22 ). Thus, the application of DDAF as a surrogate of disease severity in STGD1 may represent the trailing edge of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in hypoFAF area are currently being used as the primary outcome measure for a clinical trial involving Stargardt disease (i.e., ClinicalTrials.gov NCT03772665). Functionally, the boundary of deep scotomata often exceeds the margins of RPE atrophy in STGD1 (9). In early stages of disease, markers of disease progression have also been proposed, including the leading disease front as observed in the distribution of flecks (10), and lipofuscin accumulation measured by (quantitative) autofluorescence imaging (11)(12)(13).…”
Section: Methodsmentioning
confidence: 99%
“…The near-infrared AF images displayed intense pan-retinal hyper-autofluorescent (yellow arrows) and hypo-autofluorescent spots (red arrows), corresponding to hyper-reflective subretinal foci (yellow arrows) and hyporeflective spots (red arrows), respectively, on optical coherence tomography scans (Figure 1g). Atrophic or amelanotic RPE cells have been reported to be hypo-autofluorescent in infrared AF imaging (Duncker et al, 2014;Sunness et al, 2020). RPE atrophy was present in optical coherence tomography scans in the superior retina after FAC injection (right side of scan, yellow box).…”
Section: Fac Injection Induced Acute Pan-retinal Af and Photoreceptor Degenerationmentioning
confidence: 99%
“… 21 The latter study showed that photoreceptor dysfunction assessed by microperimetry extended peripheral to the dark lesions detected in SW-AF images. 21 The width of EZ loss in OCT scans has been compared to atrophy in NIR-AF and SW-AF findings in a study which measured abnormal reflectivity in en face slab images generated from B-scans acquired by wide-field swept-source OCT. 17 The area of the central hyperreflective zone attributable to RPE atrophy in the sub-RPE slab was in agreement with the hypoAF SW-AF area but both underestimated RPE atrophy based on the area of hypoAF in NIR-AF images. 17 The area of abnormal reflectivity attributable to EZ loss in the inner segment/outer segment (IS/OS) slab corresponded to the zone of combined hypoAF and hyperAF in SW-AF images.…”
Section: Discussionmentioning
confidence: 88%